2023
DOI: 10.1055/a-2020-6797
|View full text |Cite
|
Sign up to set email alerts
|

Risk of total metachronous advanced neoplasia at surveillance colonoscopy after detection of serrated lesions: a matched case–cohort study

Abstract: Background and Study Aims: Serrated lesions (SLs), including sessile serrated lesions (SSL) and traditional serrated adenomas (TSA) have become subject of increased interest for their role as CRC precursors. Primary aim was to evaluate the presence of total metachronous advanced neoplasia (T-MAN) at follow-up in patients with index SL compared to a matched cohort without SL. Patients and Methods: Patients 45-74y with SLs were matched 2:1 by sex; age; synchronous polyps (high-risk adenoma [HRA], low-risk adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This study is part of a larger project comparing outcomes for colonoscopy findings. Part of the study cohort has been previously reported, however, there are no data overlap in reported outcomes 15 .…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project comparing outcomes for colonoscopy findings. Part of the study cohort has been previously reported, however, there are no data overlap in reported outcomes 15 .…”
Section: Methodsmentioning
confidence: 99%
“…In this issue of Endoscopy, Djinbachian et al present a large retrospective matched case-cohort analysis of the prevalence of total metachronous advanced neoplasia (T-MAN) among patients who underwent resection of an SSL compared with patients without SSLs [7]. T-MAN is an "umbrella" outcome that includes both metachronous advanced adenomas and metachronous advanced SSLs.…”
mentioning
confidence: 99%